2010
DOI: 10.1080/13675560903286151
|View full text |Cite
|
Sign up to set email alerts
|

Critical barriers to the implementation of close supplier–buyer relationships: the case of Greek manufacturing industry

Abstract: This article presents the results of an empirical survey aimed at the following: (1) providing data for a factor analysis of the various barriers to the development and implementation of close supplier-buyer relationships and (2) detecting the degree to which the development of a quality system according to the ISO 9000 series of standards can help companies to overcome these barriers. The survey was carried out in Greek manufacturing organisations. The analysis of the results led to the detection of five crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Although as found from the literature that till now no research has reported barriers to synergistic approach (TQM-SCM) but there exist studies addressing barriers to the supplierbuyer relationship, suppliers quality and so on. For example: Gotzamani and Theodorakioglou (2010) identified the five critical barriers, namely low buyers' interest and appreciation of their suppliers, low buyers' internal integration and leadership commitment, low suppliers' interest in collaborative relationships, low buyers' interest in partnerships and dependence relationships and buyers' unwillingness and inability to change traditional supplier management practice to the successful implementation of close supplier-buyer relationships in the case of Greek manufacturing industry. Further, Mukhtar and Schiffauerova (2016) found seven most important barriers to supplier QM, namely leadership ignorance, poor human resource, lack of cooperation, low encouragement, lack of ICT, lack of green practices for production and low knowledge of world circumstances.…”
Section: Barriers To Tqm and Scm Implementationmentioning
confidence: 99%
“…Although as found from the literature that till now no research has reported barriers to synergistic approach (TQM-SCM) but there exist studies addressing barriers to the supplierbuyer relationship, suppliers quality and so on. For example: Gotzamani and Theodorakioglou (2010) identified the five critical barriers, namely low buyers' interest and appreciation of their suppliers, low buyers' internal integration and leadership commitment, low suppliers' interest in collaborative relationships, low buyers' interest in partnerships and dependence relationships and buyers' unwillingness and inability to change traditional supplier management practice to the successful implementation of close supplier-buyer relationships in the case of Greek manufacturing industry. Further, Mukhtar and Schiffauerova (2016) found seven most important barriers to supplier QM, namely leadership ignorance, poor human resource, lack of cooperation, low encouragement, lack of ICT, lack of green practices for production and low knowledge of world circumstances.…”
Section: Barriers To Tqm and Scm Implementationmentioning
confidence: 99%
“…lack of confidence, lack of collaboration intent, and so forth) to establishing effective close supplier-buyer relationships. Gotzamani and Theodorakioglou (2010) claimed in their study that these barriers are more important issues for establishing a close partnership in emerging markets than in developed countries such as Japan, the United States and Western European countries. Thus, such cultural differences might be the reason why strategic partnership has not been found to be statistically related to the operational performance in this research.…”
Section: Research Implications and Limitationsmentioning
confidence: 99%
“…The effectiveness of today's modern supply chain management can be largely attributed to IT tools such as Enterprise Resource Planning (ERP), Electronic Data Interchange (EDI), and the Internet (Akkermans et al, 2003;Hsu et al, 2008). The required information can flow between partner companies rapidly and accurately with these IT tools; thus they create a competitive advantage when compared to other supply chain networks with relatively fewer IT tools (Holweg and Pil, 2008;Paulraj et al, 2008;Gotzamani and Theodorakioglou, 2010). Important information such as product availability, inventory level and control, shipment status, new product requirements, demand forecasts and order management can be provided with appropriate IT infrastructures in real-time (Stank et al, 1999;Hsu et al, 2008;Cook et al, 2011).…”
mentioning
confidence: 99%
“…for which supplier and manufacturer are associated with each other ThengLau and Goh (2005),Handfield et al (2000),Li et al (2010),Thomas et al (2011), Wagner (2011 Lack of competent workforce (LCW) Unskilled, inexperienced and incapable workforce at the supplier's sideGotzamani and Theodorakioglou (2010), Ellram et al (2013), Kaplinsky (2014), Mohanty et al (2014) Large potential customer base (LPC) Large number of potential customers the supplier serving, i.e. division of services and inputs Handfield et al (2000), Talluri et al (2010), McIvor (2011), Hüttinger et al supplier to implement the changes in line with manufacturer's requirements Leenders (1989), Modi and Mabert (2007), Mahapatra et al (2010), Kim et al (2010), Rajesh and Ravi (2015) Poor resource capabilities (PRC) Poor resources at supplier such as lack of technological ability, information infrastructure, financial capability, etc.…”
mentioning
confidence: 99%
“…poor support to its supplier in implementing SD initiativesEmiliani (2003),Handfield et al (2000),Carr and Kaynak (2007), Talluri et al (2010) Longer outstanding payables (LOP) Longer times taken by the manufacturer in paying back the supplier for its inputs and services Emiliani (2003), Srinivasan et al (2011), Dries et al (2014) Poor supplier integration (PSI) Poor supplier involvement at right stages of value addition process Mahapatra et al (2010), Gotzamani and Theodorakioglou (2010), Talluri et al (2010), Danese (2013) Poor supplier motivation mechanisms (PSM) Lack of mechanisms designed motivating supplier participation and contribution Mahapatra et al (2010),Gotzamani and Theodorakioglou (2010),Wang (2010),Mortensen and Arlbjørn (2012) Poor supplier evaluation and feedback systems related to SD (PEF) Lack of available systems for evaluating the supplier and to collect feedbackLascelles and Dale (1990),Modi and Mabert (2007),Kumar et al (2011), Prajogo et al et al (2010,Mortensen and Arlbjørn (2012) Manufacturer's project completion exercise (MPC) Ability of a supplier to finish the project on time and fulfilling all the contracted requirementsRoutroy and Sunil Kumar (2014),Routroy and Pradhan (2014) …”
mentioning
confidence: 99%